Efficacy and Safety of Iguratimod Supplement to the Standard Immunosuppressive Regimen in Highly Mismatched Renal Transplant Recipients: A Pilot Study - Tao, Jun; Sun, Li; Wang, Zijie; Chen, Hao; Han, Zhijian; Zhang, Hengcheng; Yang, Haiwei; Huang, Zhengkai; Fei, Shuang; Ju, Xiaobin; Tan, Ruoyun; Gu, Min (Frontiers in Immunology, 2021)
Iguratimod (IGU) can mitigate the symptoms of rheumatoid arthritis through its anti-inflammatory effects. The objective of this study was to investigate the clinical efficacy and safety of IGU in highly HLA-mismatched renal transplant recipients, in combination with standard immunosuppressive regimen. This pilot study was designed as an open-label, blank-control, randomized clinical trial on patients recruited from a single transplant center in China. Patients who met the inclusion criteria were randomized to the IGU (n=27) and blank control (n=27) groups. IGU was administrated with the conventional triple immunosuppressive protocol for 52 weeks after kidney transplantation. The incidence of biopsy-proven acute rejection rate was 14.8% (4/27) in the IGU group and 29.6% (8/27) in the control group, P = 0.19. The clinical rejection rate was also substantially reduced in the IGU group (3.7% vs. 18.5%, P = 0.08). De novo donor-specific antibody also showed a decline trend in the IGU group after 52 weeks. The graft function and incidence of adverse events were similar between the two groups. In addition, IGU intervention significantly decreased the number of NK cells throughout the follow-up. In conclusion, our study has shown the possibility that IGU could reduce the allograft rejection rate and de novo DSA with appreciable safety in combination with conventional immunosuppressants. Formal clinical trials were warranted based on current findings.